Aubergine Controls Germline Stem Cell Self-Renewal and Progeny Differentiation via Distinct Mechanisms. - Ma, X.; Zhu, X.; Han, Y.; Story, B.; Do, T.; Song, X.; Wang, S.; Zhang, Y.; Blanchette, M.; Gogol, M.; Hall, K.; Peak, A.; et al. (Developmental Cell, 2017)
Piwi family protein Aubergine (Aub) maintains genome integrity in late germ cells of the Drosophila ovary through Piwi-associated RNA-mediated repression of transposon activities. Although it is highly expressed in germline stem cells (GSCs) and early progeny, it remains unclear whether it plays any roles in early GSC lineage development. Here we report that Aub promotes GSC self-renewal and GSC progeny differentiation. RNA-iCLIP results show that Aub binds the mRNAs encoding self-renewal and differentiation factors in cultured GSCs. Aub controls GSC self-renewal by preventing DNA-damage-induced Chk2 activation and by translationally controlling the expression of self-renewal factors. It promotes GSC progeny differentiation by translationally controlling the expression of differentiation factors, including Bam. Therefore, this study reveals a function of Aub in GSCs and their progeny, which promotes translation of self-renewal and differentiation factors by directly binding to its target mRNAs and interacting with translational initiation factors.